Effects of trade on employment creation and human development in developed and developing countries - Yunus, Mawar Murni (2013)
Trade, employment creation, and human development are the three major areas in the economic growth, wealth and prosperity of a country. Trade has played an increasing role in the world economy over the past decades. In both developed and developing countries, trade has created employment and higher incomes for millions. Simultaneously, many people have yet to benefit. According to UNDP (2006), trade can definitely enhance human development. Human development is a process of enlarging people's choices. It puts the importance on the three essentials for people; to lead a long and healthy life, to obtain knowledge, and to have right to use resources needed for a decent standard of living and their environment. If these essential choices are not offered, many other opportunities remain inaccessible. The Human Development Index (HDI) has become a standard for measuring human development. Its component indices measure life expectancy, literacy and education, and GDP per capita. The purpose of this study is to examine the effect of trade on employment creation, human development, health, and education in developed and developing countries. Firstly, for the effect of trade on employment creation, this study explores whether improvement in trade in developed and developing countries can create or destroy employments. Secondly, for the impact of trade on human development, this study seeks to address does trade affect human development or not. Moreover, this study attempts to evaluate which channels such as, income, employment, or institutional quality, might influence human development. Furthermore, in studying the effect of trade on health and education, this study examines whether the improvement in trade has a good or bad effect on health and education. A systematic empirical study based on the Generalized Method of Moments (GMM) has been undertaken by this study. In the first issue, this study concentrates on the time frame from year 1980 to 2009 of 81 countries; 30 developed countries and 51 developing countries. In the other two issues, this study focuses on the time frame from year 1980 to 2007 with 90 countries; 32 and 58 countries from developed and developing countries, respectively. The results in the first issue clearly indicate that total trade which consists of exports and imports is insignificant in promoting employment creation for developing countries. However, the export equation found a positive effect of export on employment creation in developing countries. Nevertheless, the import equation suggests a negative effect of import on employment creation in developed countries. On the other hand, the empirical results for the effect of trade on human development demonstrate that total trade does not affect human development. The employment channel results found a positive role in influencing the effect of total trade on human development in developed countries. Overall, for the three channels such as income, employment, and institutions, improvement in total trade does not influence human development for developing countries. The results for the last issue evidently indicate that total trade has a negative effect on health in developing countries. Furthermore, the trade and education results indicate that total trade does not influence education. The empirical result states that export is statistically a significant determinant for the employment creation in developing countries, whereas import is statistically a significant determinant of employment creation in developed countries. Furthermore, the empirical result also shows that employment channel is statistically a significant determinant for the human development in developed countries. Hence, trade should be emphasized if employment creation and human development are to be considered as valid policy objective. Specifically, to create employment, the main policy should focus on both the improvement of exports in developing countries. At the same time, the developed countries need to produce and remain goods and services for the domestic purposes particularly for the industries which have comparative advantage in their productions. As to improve the human development, the policy should concentrate on both formal and informal education such as learning and upgrading skills respectively.